Enhancing the Professional Skills Development Project (MESGEP): An Attempt to Facilitate Ecological Awareness - YILMAZ, Adem (Participatory Educational Research (Per), 2024)
Concepts change at an incredibly fast rate for human beings and more specifically in the world of education and whence for society. To cite an example, there exist conceptualizations ‘issued’ such as Industry 4.0 or University 5.0. The very standpoint here arguably directs the focus to andragogy “at the brink of the post-anthropocene” (Wallin, 2017) in a rather inevitable fashion. Integrating the salient elements of the notion post-anthropocene into andragogy of Vocational Education and Training (VET) and ensuring the ‘sustainability’ of learning and teaching related practicum in this regard is deemed essential considering “growing ecological awareness in the era of the Anthropocene could also productively influence all spheres of life-ecology, economics, education, politics and the social sphere–in the interest of sustaining the planet” (Le Grange, 2019, p.1). In this direction, this paper intends to discuss the optimal means through which the VET given to the marginal groups in Türkiye as part of a project entitled “Professional Skills Development Project (MESGEP)” can be enriched towards raising an awareness about the climate crisis and about the other ecological issues awaiting to be confronted. It is hoped that with the new amendments to made to the available curricula, the individuals as the participants of the project can gain more consciousness about ecological crises and adopt the relevant skills. Thereupon, it is thought that educating disadvantaged groups in this way will not only point to equal opportunity in education but also attempt to alter the previously held belief, which pinpointed environmental pollution is indeed an externality of education.
Keywords: Information Systems (Other); Bilgi Sistemleri (Diğer); Professional skills; post-anthropocene; education of individuals; disadvantaged groups; marginal groups; 13. Climate action; 9. Industry and infrastructure; 11. Sustainability; 10. No inequality